Risk assessment and photo-disinfection of antibiotic residues and antibiotic-resistant bacteria in water sources from Ede, Nigeria - Gloria O. Taylor; Aemere Ogunlaja; Olumide D. Olukanni; Oluwatosin M. Awopetu; Frances Okodua; Daniel O. Godson; Afolarin Otusile; Daniella Ekpe; Esther Deguenon; Kevin M. Sintondji; Victorien Dougnon; Olumuyiwa O. Ogunlaja; et al. (Heliyon)
Environmental antibiotic residues (EARs) and antibiotic-resistant bacteria (ARB) are known to contribute to global antimicrobial resistance (AMR). This study investigated EAR levels in selected wells, river, abattoir wastewater, bottled water and sachet water from Ede, Nigeria. Ecological risk quotient (RQ) and health risk (Hazard quotient) of the levels of these EARs, ARB and multidrug-resistant bacteria (MDR) with their antibiotic resistance were calculated. Antibiotic residues detected included tetracycline-TET (14.2–135.8 μg/L), chloramphenicol-CHL (6.8–224.7 μg/L), metronidazole-MET (3.7–83.8 μg/L), sulfamethoxazole-SUL (0.56–18.6 μg/L), and ciprofloxacin-CIP (3.8–97 μg/L). Antibiotic residues in STW samples were below the detection limit while ampicillin was not detected in any of the water samples. Chloramphenicol posed the highest ecological risk to algae while infants were particularly at risks of ciprofloxacin and metronidazole resistance in various water sources. No health risk due to bottled water exposure is observed for any population group. The mean log10 bacteria count (cfu/mL) followed the trend abattoir (5.68) > river (5.67) > hand-dug well (5.53) > sachet (5.03) > bottled (4.83). The most occurring ARB in water samples are Bacillus spp (36.3 %) > Staphylococcus (27.5 %) and the most dominant MDR isolate is Bacillus cereus. All isolates exhibited 62.5, 100, 31.3, 77.5, 58.8 and 33.8 % resistance to AMP, MET, CIP, TET, CHL and SUL, respectively. Visible-light composite material (Cu/Zn-doped delaminated kaolinite) completely disinfected 12.5 and 15.8 L of water containing Log10 7.5 cfu/mL of ARB Enterobacter sp and Bacillus sp respectively with no regrowth in treated water after storage for three days. Levels of EAR in the water sources in this study are among the highest in aquatic systems worldwide and can potentially lead to community AMR. Usage, discharge and sales of antibiotics should be guided by policies while routine monitoring of drinking water sources should be encouraged to reduce the AMR burden in the region. The photocatalytic material used in this study for water disinfection offers a promising, cost-effective solution for mitigating AMR risks from drinking water.